Jane Tolmach for California Assembly 36th District: Instructions for Precincit Volunteers
This document provides instructions for precinct volunteers working on Jane Tolmach's Assembly campaign. It outlines a phone script for contacting voters, asks volunteers to categorize each household's level of support, and directs them to record names and contact information of those willing to help. Volunteers are encouraged to recruit supporters for activities such as precinct walking, distributing literature, posting yard signs, attending the Brown reception, phone banking on election day, working in headquarters, and contributing funds. The instructions emphasize timely return of lists and coordination with campaign headquarters to maximize get-out-the-vote efforts.